UKRAINE'S PARTICIPATION IN THE INTERMARIUM PROJECT IMPLEMENTATION IN THE CONTEXT OF THE STRATEGIC PARTNERSHIP OF UKRAINE AND POLAND (Вісник: Міжнародні відносини, 2024)
Background. The authors of the article investigate the participation of Ukraine in the Intermarium project implementation in context of the strategic partnership between Ukraine and Poland. The search for a new security architecture and regional cooperation has forced national elites in Poland and Ukraine to reconsider their efforts on regional and security cooperation.Methods. Analytical, historical, and generalization methods were used. During the research, the team of authors relied on the principle of objectivism.Results. It is substantiated that in the context of increasing threats to Ukrainian foreign policy and diplomacy, Ukraine should work more deeply in the direction of intensifying relations with Eastern European countries regarding the creation of a platform for security dialogue within the Baltic-Black Sea Commonwealth. It has been proven that the coordination of cooperation at different levels in the Mediterranean region will allow to optimize and strengthen the level of national security of Ukraine, Poland and other states of Central and Eastern Europe.Conclusions. The need to intensify trade and logistics cooperation and the perception of the threat emanating from the Russian Federation became the main reasons for returning to the idea and its institutionalization within the framework of the Intermarium. Participation in the Three Seas Initiative can serve as an additional link for Ukraine, which contributes to the European and Euro-Atlantic integration of Ukraine and the macro-regional level.
Keywords: Intermarium, Baltic-Black Sea Commonwealth, Three Seas Initiative, Ukraine, Poland, national security, Russian Federation, aggression, Central and Eastern Europe